Словарь сокращений русского языка: Ок. 17700 сокр. / Д. И. Алексеев, И. Г. Гозман, Г. В. Сахаров - Алексеев Дмитрий Иванович (Рус. яз., 1984)
На пер. авт. не указаны Экземпляры: (20200413) / Инвентарный номер: 8465 / Сис.шифр: 4Р / Авт.знак: А47 / ББК: 4Р-03